Fabrication of an In Situ pH-Responsive Raloxifene-Loaded Invasome Hydrogel for Breast Cancer Management: In Vitro and In Vivo Evaluation - Hanan O. Farouk; Marwa M. Nagib; Amr Gamal Fouad; Demiana M. Naguib; Sherif Faysal Abdelfattah Khalil; Amany Belal; Samar F. Miski; Nisreen Khalid Aref Albezrah; Shatha Hallal Al-Ziyadi; Gi-Hui Kim; Ahmed H. E. Hassan; Kyung-Tae Lee; et al. (Pharmaceuticals)
Background/Objectives: Raloxifene (RLF) is a therapeutic option for invasive breast cancer because it blocks estrogen receptors selectively. Low solubility, limited targeting, first-pass action, and poor absorption are some of the challenges that make RLF in oral form less effective. This study aimed to create an intra-tumoral in situ pH-responsive formulation of RLF–invasome (IPHRLI) for breast cancer treatment, with the goals of sustaining RLF release, minimizing adverse effects, and enhancing solubility, bioavailability, targeting, and effectiveness. Methods: Numerous RLF–invasome formulations were optimized using design expert software (version 12.0.6.0, StatEase Inc., Minneapolis, MN, USA). Integrating an optimal formulation with an amalgam of chitosan and glyceryl monooleate resulted in the IPHRLI formulation. In vivo testing of the IPHRLI formulation was conducted utilizing the Ehrlich cancer model. Results: Requirements for an optimum RLF–invasome formulation were met by a mixture of phospholipids (2.46%), ethanol (2.84%), and cineole (0.5%). The IPHRLI formulation substantially sustained its release by 75.41% after 8 h relative to free RLF. The bioavailability of intra-tumoral IPHRLI was substantially raised by 4.07-fold compared to oral free RLF. Histopathological and tumor volume analyses of intra-tumoral IPHRLI confirmed its efficacy and targeting effect. Conclusions: the intra-tumoral administration of the IPHRLI formulation may provide a potential strategy for breast cancer management.